The Central Park Five : the untold story behind one of New York city's most infamous crimes - Burns, Sarah, 1982- (New York : Vintage Books, 2012)
On April 20th, 1989, two passersby discovered the body of the""Central Park jogger" crumpled in a ravine.. She'd been raped and severely beaten. Within days five black and Latino teenagers were apprehended, all five confessing to the crime. The staggering torrent of media coverage that ensued, coupled with fierce public outcry, exposed the deep-seated race and class divisions in New York City at the time. The minors were tried and convicted as adults despite no evidence linking them to the victim. They served their complete sentences before another man confessed. Over a decade later, when DNA tests connected serial rapist Matias Reyes to the crime, the government, law enforcement, social institutions and media of New York were exposed as having undermined the individuals they were designed to protect. Here, the author recounts this historic case for the first time since the young men's convictions were overturned, telling, at last, the full story of one of New York's most legendary crimes. Intertwining the stories of these five young men, the police officers, the district attorneys, the victim, and Reyes, she unravels the forces that made both the crime and its prosecution possible
Originally published with the subtitle "The chronicle of a wilding" by Random House, c2011
Includes bibliographical references (p. 215-228) and index
Keywords: Rape victims -- New York (State) -- New York; Violent crimes -- New York (State) -- New York; Judicial error -- New York (State) -- New York; Criminal justice, Administration of -- New York (State) -- New York